Yersinia pestis Ail: multiple roles of a single protein - Kolodziejek, Anna M.; Hovde, Carolyn J.; Minnich, Scott A. (Frontiers in Cellular and Infection Microbiology, 2012)
Yersinia pestis is one of the most virulent bacteria identified. It is the causative agent of plague – a systemic disease that has claimed millions of human lives throughout history. Y. pestis survival in insect and mammalian host species requires fine-tuning to sense and respond to varying environmental cues. Multiple Y. pestis attributes participate in this process and contribute to its pathogenicity and highly efficient transmission between hosts. These include factors inherited from its enteric predecessors; Y. enterocolitica and Y. pseudotuberculosis, as well as phenotypes acquired or lost during Y. pestis speciation. Representatives of a large Enterobacteriaceae Ail/OmpX/PagC/Lom family of outer membrane proteins (Omps) are found in the genomes of all pathogenic Yersiniae. This review describes the current knowledge regarding the role of Ail in Y. pestis pathogenesis and virulence. The pronounced role of Ail in the following areas are discussed i) inhibition of the bactericidal properties of complement, ii) attachment and Yop delivery to host tissue iii) prevention of PMNL recruitment to the lymph nodes, and iv) inhibition of the inflammatory response. Finally, Ail homologs in Y. enterocolitica and Y. pseudotuberculosis are compared to illustrate differences that may have contributed to the drastic bacterial lifestyle change that shifted Y. pestis from an enteric to a vector-born systemic pathogen.